Fiasco : the American military adventure in Iraq - Ricks, Thomas E. (New York : Penguin Press, 2006)
[In this book, the author offers an] account - explosive, shocking, and authoritative - of the American military's tragic experience in Iraq. [The book also offers] accounts of battles such as 2nd Fallujah and Tall Afar, whose names should take their place alongside two Jima and Porkchop Hill on a select list of honor ... Too many American and Iraqi lives have been lost, and too much of America's might and influence has been squandered, for these individuals to escape a fair reckoning. [This book] is that reckoning.-Dust jacket.
Containment -- A bad ending -- Containment and its discontents -- This changes everything: the aftermath of 9/11 -- The war of words -- The run-up -- The silence of the lambs -- Into Iraq -- Winning a battle -- How to create an insurgency (I) -- How to create an insurgency (II) -- The CPA: "can't produce anything" -- Getting tough -- The descent into abuse -- The long term -- "The Army of the Euphrates" takes stock -- The Marine Corps files a dissent -- The surprise -- The price paid -- The corrections -- Turnover -- Too little too late? -- Betting against history.
Includes bibliographical references (pages 441-462) and index.
Keywords: Iraq War, 2003-2011.; United States -- History, Military -- 21st century; Guerre en Irak, 2003-; Histoire militaire; Iraq; United States; Irakkrieg; USA; Iraq War, 2003-2011.; United States -- Military history; 2000-2099; Geschichte -- 2003-2006; Iraq War, 2003-; Iraq War, 2003- -- Personal narratives, American; United States -- History, Military -- 21st century; Military history